INDONESIAS DEMOGRAPHIC DIVIDEND OR WINDOW OF OPPORTUNITY? - Mayling Oey Gardnier; Peter Gardnier (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2013)
As the worlds fourth largest populous nation, Indonesia is predicted to reach theheight of its so-called demographic dividend between 2020 and 2030 when the shareof population in working ages will be at its highest level and the potential for increasedoutput per capita and hence more productive investment will theoretically be at itspeak. But the ability to maximize this potential is far from certain and depends on avariety of social and economic underpinnings, including key issues associated withhuman resource capacity and gender equality that will determine how well Indonesiais placed to meet the challenges involved. This contribution first reviews the historyof demographic and social transformations, including the dramatic shift from anti- topro-natalist policies that have occurred in Indonesia since independence. Set againsta deterministic trend of an age-sex specific population projection, we seek to providean assessment of these past trends in demographic and social dynamics in relationshipto the current state of preparedness, with a focus on social and gender-related issues.Finally, we will outline several of the key challenges, particularly in the context of thecurrent socio-economic and political climate that will ultimately determine whetherIndonesia will move into a future real demographic dividend or only observe the worldthrough a window of opportunity.Keywords: Demographic dividend, Population, Labour, Pro-natalist policies